Isotopic evidence of partial mycoheterotrophy in Burmannia coelestis (Burmanniaceae). Issue 1 (23rd November 2015) - Bolin, Jay F.; Tennakoon, Kushan U.; Majid, Mohamed Bin Abdul; Cameron, Duncan D.
Abstract: The Burmanniaceae contain several lineages of achlorophyllous mycoheterotrophic plants that associate with arbuscular mycorrhizal fungi (AMF). Here we investigate the isotopic profile of a green and potentially mycoheterotrophic plant in situ, B urmannia coelestis, and associated reference plants. We generated δ 13 C and δ 15 N stable isotope profiles for five populations of B . coelestis . B urmannia coelestis was significantly enriched in 13 C relative to surrounding C3 reference plants and significantly depleted in 13 C relative to C4 reference plants. No significant differences were detected in 15 N enrichment between B . coelestis and reference plants. The isotopic profiles measured are suggestive of partial mycoheterotrophy in B . coelestis . Within the genus Burmannia transitions to full mycoheterotrophy have occurred numerous times, suggesting that some green B urmannia species are likely to be partially mycoheterotrophic but in many conditions this mode of nutrition may only be detectable using natural abundance stable isotopic methods, such as when associated with C4 mycorrhizal plants. Abstract : This study provides the first evidence of partial mycoheterotrophy in a green Burmanniaceae using natural abundance stable isotope methods. Associated mycorrhizal plants with C4 metabolism probably provided the enriched d13C signature in Burmannia coelestis .